The validity of health-related quality of life questionnaires in bronchiectasis: a systematic review and meta-analysis. Issue 8 (11th February 2016) - Spinou, Arietta; Fragkos, Konstantinos C; Lee, Kai K; Elston, Caroline; Siegert, Richard J; Loebinger, Michael R; Wilson, Robert; Garrod, Rachel; Birring, Surinder S
Abstract : Background: A range of questionnaires have been used to assess health-related quality of life (HRQOL) in bronchiectasis. A systematic review was conducted to evaluate their psychometric properties and assess associations between HRQOL and clinical measures. Methods: Five electronic databases were searched. Studies eligible for inclusion were those that investigated the validity of HRQOL questionnaires and/or their association with other outcomes in adults with bronchiectasis. Patients with cystic fibrosis were excluded. The identified questionnaires were assessed for convergent, discriminant and cross-cultural translation validity; missing data, floor and ceiling effects, internal consistency, responsiveness and test-retest reliability. A meta-analysis was conducted to estimate the strength of associations between HRQOL and clinical measures. Results: From 1918 studies identified, 43 studies were included in the systematic review, of which 38 were suitable for the meta-analysis. Nine HRQOL questionnaires were identified, with the most widely used being: St George's Respiratory Questionnaire, Leicester Cough Questionnaire, Quality of Life–Bronchiectasis and Short Form-36. HRQOL questionnaires had moderate to good internal consistency and good test-retest reliability. Only 8 of 18 studies that used translated HRQOL questionnaires reported or referred to the validity of the translated questionnaire. There was a stronger correlation (mean r (95% CI)) between HRQOL and subjective outcome measures, such as dyspnoea (0.55 (0.41 to 0.68)) and fatigue (0.42 (0.23 to 0.58)) compared with objective measures; exercise capacity (−0.41 (−0.54 to −0.24)), FEV1 % predicted (−0.31 (−0.40 to −0.23)) and extent of bronchiectasis on CT scan (0.35 (0.03 to 0.61)); all p<0.001. Conclusions: This review supports most HRQOL questionnaires used in bronchiectasis have good psychometric properties. There was a weak to moderate association between HRQOL and objective outcome measures. This suggests that HRQOL questionnaires assess a unique aspect of health not captured by objective measures.